2018
DOI: 10.3389/fnagi.2018.00348
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and Pharmacological Role of Liquiritigenin and Isoliquiritigenin From Radix Glycyrrhizae in Human Health and Disease Models

Abstract: The increasing lifespan in developed countries results in age-associated chronic diseases. Biological aging is a complex process associated with accumulated cellular damage by environmental or genetic factors with increasing age. Aging results in marked changes in brain structure and function. Age-related neurodegenerative diseases and disorders (NDDs) represent an ever-growing socioeconomic challenge and lead to an overall reduction in quality of life around the world. Alzheimer’s disease (AD) and Parkinson’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(86 citation statements)
references
References 133 publications
2
84
0
Order By: Relevance
“…Numerous natural dietary phytochemicals have been observed to inhibit carcinogenesis and have attracted growing interest as complementary and alternative medicines as well as for cancer chemoprevention due to their wide availability, mildness, and low toxicity [11]. Glycyrrhiza species (licorice) are widely used as herbal medicine in Asia, as they exhibit highly effective antitussive, expectorant, and antipyretic activities [12,13]. Among the bioactive ingredients isolated from licorice, isoliquiritigenin (ISL; 2 ,4,4 -trihydroxychalcone) has been reported to exert considerable biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous natural dietary phytochemicals have been observed to inhibit carcinogenesis and have attracted growing interest as complementary and alternative medicines as well as for cancer chemoprevention due to their wide availability, mildness, and low toxicity [11]. Glycyrrhiza species (licorice) are widely used as herbal medicine in Asia, as they exhibit highly effective antitussive, expectorant, and antipyretic activities [12,13]. Among the bioactive ingredients isolated from licorice, isoliquiritigenin (ISL; 2 ,4,4 -trihydroxychalcone) has been reported to exert considerable biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…The flavonoid 4,2′,4′-trihydroxichalcone, also known as isoliquiritigenin (IsoLQ) ( Figure 1 ), proceeds from the roots and rhizomes of licorice ( Glycyrrizha glabra ). It is used in Asia as an herbal medicine due to its anti-inflammatory, antimicrobial, antitumoral, and antioxidant properties [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Regarding its antioxidant activity, it has been reported that IsoLQ scavenges reactive oxygen species (ROS), such as the superoxide anion (O 2 ●− ), hydroxyl radical, hydrogen peroxide, and singlet oxygen [ 4 , 7 ], and induces phase II cytoprotective enzymes’ expression [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…MS/MS fragmentation in the negative ion mode revealed fragment ions at m/z 417.1189, 255.0660, 135.0078 and 119.0494. Based on CD software prediction and related literature (Ramalingam, Kim, Lee, & Lee, ), M13 and M14 were identified as glucuronidated products of liquiritin and isoliquiritin, respectively.…”
Section: Resultsmentioning
confidence: 99%